Synthesis and in vitro evaluation of [18F]FECIMBI-36: A potential agonist PET ligand for 5-HT2A/2C receptors. Issue 18 (15th September 2015) - Prabhakaran, Jaya; Underwood, Mark D.; Kumar, J.S. Dileep; Simpson, Norman R.; Kassir, Suham A.; Bakalian, Mihran J.; Mann, J. John; Arango, Victoria
Graphical abstract